The Rights to Review Policy Rules in the Perspective of Rule of Law - Ida Hanifah; Andryan Andryan (Law and Human Rights Policy Strategy Agency, Ministry of Law and Human Rights of The Repub, 2021)
The State of Indonesia is a country based on law, this is as confirmed in Article 1 paragraph (3) of the 1945 Constitution, the State of Indonesia is a rule of law. Policy rules only function as part of the operational implementation of government tasks. This research used normative juridical research method, namely research in which the study refers to and bases on legal norms and rules. The statutory approach was used to look at the issue of the right to review policy rules. The conceptual approach was used to look at the conception of reviewing policy rules in the concept of rule of law. Policy rules are not a type of laws and regulations, the right to review laws and regulations cannot be applied to policy rules. The review of policy rules is more directed at doelmatigheid and the touchstone is the general principles of proper governance. The Supreme Court cannot review policy rules. Arrangements are needed to realize the protection for the parties who are harmed due to a policy rule, so that it can be in accordance with the concept of rule of law.